The specifics of the components of physical fitness in student wrestlers specializing in freestyle and Greco-Roman styles - Laptev A.I.; Tarakanov B.I.; Apoiko R.N.; Shevtsov A.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is a comparative analysis of the physical fitness of student wrestlers engaged in freestyle and Greco-Roman wrestling. Methods and structure of the study. The study involved 81 university-trained athletes specializing in wrestling. The group consisted of 47 Greco-Roman wrestlers (average age 17.5±2.4 years) and 34 freestyle wrestlers (average age 17.5±1.6 years). All participants were students studying at physical education and sports colleges and universities. The following methods were used to conduct the study: anthropometric measurements and bioimpedance analysis, as well as ergometric tests. In addition, the strength indicators of the muscles of the upper and lower extremities were assessed. Results and conclusions. The analysis of anthropometric data and body composition revealed no significant differences between wrestlers of different styles. However, when assessing the anaerobic power of the arm muscles, Greco-Roman wrestlers showed significantly better results compared to freestyle wrestlers. This is due to the fact that in Greco-Roman wrestling, hand actions are more important, which affects the characteristics of their physical fitness and tactics. At the same time, despite the concession in the anaerobic power of the arm muscles, freestyle wrestlers demonstrate an advantage in most speed and strength characteristics. This reflects a wider range of techniques and a balanced development of physical qualities in athletes of this style.